Improvement of the cultivation technology of spring oilseed rape for oilseeds in the south of the Non-blackearth (chernozem) zone - S. A. Devyatkin; T. F. Devyatkina; R. F. Batorshin; D. V. Bochkarev (Зерновое хозяйство России)
The purpose of the current study was to determine the efficiency of growth regulators of retardant action “Reggie”, “VRK” (a. v. chlormequat chloride, 750 g/l) and “Kolosal”, “KE” (a. v. tebuconazole, 250 g/l), as well as their tank mixtures for the spring oil seed rape (Brassica napus oleifera D. С.) variety “Neman”. The trials were carried out in 2017-2019 on leached chernozem in the forest-steppe part of the south of the Non-blackearth (chernozem) zone. There has been identified a significant effect of the studied retardants on an increase of a number of off-shoots and seeds per plant, an improvement of 1000-seed weight, a decrease of oil seed rape lodging, which provided a yield rise from 10 to 45%, compared with the control variety. The maximum productivity of spring oil seed rape (3.78 t/h) was obtained by joint treatment of crops with “Kolosal”, “KE” at a dose of 1 l/ha and “Reggie”, “VRK” at a dose of 1 l/ha, which was on 1.25 t/ha higher than in the control variant. The profitability of production on this option was 120%, with the obtained additional income of 23 thousand rubles/ha.